Adaptation of Competitive Cooperative Strategy Based on Blockchain Technology to Improve the Efficiency of Governability - Kirill A. Neverov (Евразийская интеграция: экономика, право, политика, 2019)
The article considers the possibility of applying a competitive cooperative strategy (coopetition) to improve the effi ciency of governability. The coopetition strategy in this case is considered to be based on the blockchain technology. To achieve this goal, various approaches to governability, the coopetition strategy, as well as the applicability of the blockchain technology as a basis for the practical implementation of this strategy are analyzed. A new institutionalism is used as a methodology, and game theory methods are used. In this paper, an analysis of competitive and cooperative strategy and technology of blockchain was carried out in order to identify their applicability to improve the effi ciency of governability. As a result, factors have been identifi ed that prove the positive impact of the competitive-cooperative strategy based on the blockchain on the effectiveness of governability, as well as factors at this stage of the study that do not guarantee the full applicability of the above strategy in solving the tasks of political governance.